2014
DOI: 10.1038/gim.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Appreciating the broad clinical features of SMAD4 mutation carriers: a multicenter chart review

Abstract: Heterozygous loss-of-function (LOF) SMAD4 mutations are associated with juvenile polyposis syndrome (JP) and hereditary hemorrhagic telangiectasia (HHT). Some carriers exhibit symptoms of both conditions, leading to the name JP-HHT syndrome. Three families have been reported with connective tissue abnormalities. In order to better understand the spectrum and extent of clinical findings in SMAD4 carriers, medical records of 34 patients (20 families) from five clinical practices were reviewed. Twenty-one percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 54 publications
(50 reference statements)
3
47
1
1
Order By: Relevance
“…However, some pilot studies have shown ENG germ line mutations to be associated with early‐onset JPS . Patient with JPS can have different phenotypic variations with same gene mutation, one such variant being a combined syndrome of JPS and hereditary hemorrhagic telangiectasia (JPS/HHT) with SMAD4 pathogenic variant . Furthermore, variations in polyp burden are also known to exist with JPS as some patients develop 4 to 5 polyps over lifetime and others may have more than 100 at a very young age itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some pilot studies have shown ENG germ line mutations to be associated with early‐onset JPS . Patient with JPS can have different phenotypic variations with same gene mutation, one such variant being a combined syndrome of JPS and hereditary hemorrhagic telangiectasia (JPS/HHT) with SMAD4 pathogenic variant . Furthermore, variations in polyp burden are also known to exist with JPS as some patients develop 4 to 5 polyps over lifetime and others may have more than 100 at a very young age itself.…”
Section: Discussionmentioning
confidence: 99%
“…2 Patient with JPS can have different phenotypic variations with same gene mutation, one such variant being a combined syndrome of JPS and hereditary hemorrhagic telangiectasia (JPS/HHT) with SMAD4 pathogenic variant. 3,4 Furthermore, variations in polyp burden are also known to exist with JPS as some patients develop 4 to 5 polyps over lifetime and others may have more than 100 at a very young age itself. Therefore, it becomes important to identify family-specific pathogenic variant to offer appropriate molecular genetic testing on atrisk family members in decades of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMAD4 mutations are associated with more severe upper gastrointestinal disease 17 and, in some families, with arterio-venous malformations that can result in hereditary haemorrhagic telangiectasia. 18 Both SMAD4 and BMPR1A act in the bone morphogenetic protein signalling (BMP) pathway, which is related to the TGF-beta pathway. BMP signalling is thought to be a pro-differentiation force in the normal intestinal crypt, and its attenuation by germline mutation may favour proliferation and/or a stem cell phenotype.…”
Section: A Summary Of the Colorectal Polyposis Syndromesmentioning
confidence: 99%
“…They commonly bleed, and patients often have iron deficiency anemia. 109 The polyps in JPS are made up of mucin-filled cysts lined by a columnar epithelium with an inflammatory infiltrate ( Figure 5B). A clinical diagnosis of JPS can be made when 3 or more juvenile polyps are present.…”
Section: Juvenile Polyposis Syndromementioning
confidence: 99%